Association between history of abortion and current use of contraceptives among Mongolian Women - Yohane V. A. Phiri; Gunchmaa Nyam; Yuniar Wardani; Doreen Phiri; Kun-Yang Chuang; Hsing Jasmine Chao; Owen Nkoka (BMC, 2022)
Abstract Background Understanding the factors associated with the adoption of contraceptive methods among women of childbearing age is imperative to improving maternal health outcomes. This study aimed at exploring the association between history of abortion and contraceptive use among Mongolian women. Materials and methods We analyzed cross-sectional data of 8373 women aged 15-49 years from the 2018 Mongolian Social Indicator Sample Survey (MSISS). Binary logistic regression models were used to assess the association between abortion history and current contraceptive use while accounting for both individual- and community- level factors. Results A total of 4347 (51.92%) and 2525 (30.16%) reported current use of various contraceptive methods and a history of abortion in their lifetime, respectively. Women with a history of abortion were less likely to report current use of contraceptives (adjusted odds ratio (AOR) = 0.72, 95% confidence interval (CI) [0.58-0.89]). Specifically, women with a history of abortion were less likely to report use of IUD (AOR = 0.79, 95% CI [0.71-0.90)]) and injectables (AOR = 0.59, 95% CI [0.41-0.84]). History of abortion was associated with increased likelihood of using abstinence (OR = 1.82, 95% CI [1.31-2.53]) as a contraceptive method. Conclusion Our results demonstrated a significant association between history of abortion and contraceptive use. Public health interventions aiming to improve maternal health outcomes through contraceptive use should target women with a history of abortion to improve their uptake.